Markups, profit shares, and cost-push-profit-led inflation - Michalis Nikiforos; Simon Grothe; Jan Weber (Levy Economics Institute of Bard College, 2024)
The post-pandemic surge in inflation was accompanied by a surge in the corporate share of profits. As a result, several economists and policy makers have given to it names such as "profit-led inflation" or "sellers' inflation." The present paper discusses the extent to which profit-led inflation, as an explanation for the recent surge in inflation, is compatible with what we know about the price-setting behavior of firms, income distribution, and inflation. We do that in juxtaposition to two recent critiques: that the increase in the profit share is the result of cyclical factors, and that the increase in import prices leads to higher profit shares even under constant markups. We show that there is little evidence that the recent surge in profitability is cyclical in nature. Moreover, after outlining the Structuralist/Kaleckian theories of prices and inflation we argue that profit-led inflation does not require an increase in the markup of the firms and is consistent with these theories. In the face of large import and other price shocks even under constant markups, firms are able to pass the burden of adjustment to real wages. Thus, the term profit-led emphasizes the distributional source and consequences of inflation. We also provide an empirical examination of the markups in the post-pandemic period using data from the Compustat database. We show that, on average, firms were able to increase or maintain their markups, although there is significant heterogeneity across sectors or the position of the firms in the distribution of markups.
Keywords: E11; E12; E31; C67; 330; Inflation; Markup; Distribution; Profit-led Inflation